Biopolymer-Based Functional Membranes for CO₂ Capture: Fundamentals, Sustainable Material Design, and Emerging Composite Strategies - Rini Perdana (CV. Science Tech Group, 2026)
The increasing concentration of atmospheric carbon dioxide (CO₂) has intensified the need for sustainable, energy-efficient, and scalable capture technologies. Membrane-based CO₂ capture has attracted considerable attention due to its compact configuration, continuous operation, and relatively low energy demand compared with conventional absorption processes. However, many polymeric membranes still face limitations related to the permeability–selectivity trade-off, poor humidity tolerance, weak mechanical stability, and limited CO₂ affinity. In this context, biopolymer-based functional membranes have emerged as promising platforms because of their renewable origin, processability, biodegradability, and tunable surface chemistry. This review discusses the fundamentals and recent progress of biopolymer-based membranes for CO₂ capture, focusing on the relationship between membrane composition, molecular interaction, and capture performance. Key mechanisms, including physisorption, chemisorption, carbamate and bicarbonate formation, and facilitated transport, are highlighted to explain CO₂ uptake and selective transport in functional membrane systems. Special attention is given to cellulose acetate, chitosan, poly(vinyl alcohol)-based matrices, nanocellulose-reinforced membranes, and amine-functionalized composite strategies. The roles of porous fillers, amine immobilization, interfacial compatibility, water stability, and regeneration behavior are critically discussed. Although biopolymer-based membranes offer strong potential for sustainable CO₂ capture, challenges remain in long-term cyclic stability, humid mixed-gas operation, filler dispersion, and scale-up fabrication. The development of sustainable, low-cost, and regenerable CO₂ capture membranes can contribute directly to mitigating climate change, reducing atmospheric greenhouse gas concentrations, supporting net-zero emission targets, and advancing SDG 13 (Climate Action) and SDG 7 (Affordable and Clean Energy).